Sports criminology : a critical criminology of sport and games - Groombridge, Nic (Bristol : Policy Press, 2016)
This is the first book to provide a critical criminological perspective on sport and the connections between sport and crime. Part of the New Horizons in Criminology series, it draws on the inter-disciplinary nature of criminology and incorporates emerging perspectives like social harm, gender and sexuality, and green criminology.
Title from publisher's bibliographic system (viewed on 05 Apr 2022).
Keywords: Criminology; Sports -- Law and legislation; Sports -- Sociological aspects; Crime prevention